2019
DOI: 10.1021/jacs.9b09194
|View full text |Cite
|
Sign up to set email alerts
|

Multistructural Anharmonicity Controls the Radical Generation Process in Biofuel Combustion

Abstract: The OH radical plays an important role in combustion, and isopentanol (3-methylbutan-1-ol) is a promising sustainable fuel additive and second-generation biofuel. The abstractions of H atoms from fuel molecules are key initiation steps for chain branching in combustion chemistry. In comparison with the more frequently studied ethanol, isopentanol has a longer carbon chain that allows a greater number of products, and experimental work is unavailable for the branching fractions to the various products. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…The choice of DFT is motivated by its favorable compromise between accuracy and computational cost, a property of utmost importance in the study of reaction , which includes large molecular systems with many conformers. ,,,, Specifically, it is well-known that the accuracy of the barrier heights for hydrogen abstraction will depend on the choice of the exchange–correlation functional. The Minnesota family of functionals are known to have a good performance in describing the reactivity of VOCs. ,,, ,,, Although in this particular context M06-2X is generally used more often than M08-HX, the latter functional has recently been employed in accurate MS-VTST and MP-VTST rate constant calculations ,, of atmospheric reactions. M08-HX has mean unsigned errors (MUEs) of 1.00 and 0.73 kcal mol –1 for the DBH76 and HTBH38 data sets involving hydrogen-transfer barrier heights, respectively .…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of DFT is motivated by its favorable compromise between accuracy and computational cost, a property of utmost importance in the study of reaction , which includes large molecular systems with many conformers. ,,,, Specifically, it is well-known that the accuracy of the barrier heights for hydrogen abstraction will depend on the choice of the exchange–correlation functional. The Minnesota family of functionals are known to have a good performance in describing the reactivity of VOCs. ,,, ,,, Although in this particular context M06-2X is generally used more often than M08-HX, the latter functional has recently been employed in accurate MS-VTST and MP-VTST rate constant calculations ,, of atmospheric reactions. M08-HX has mean unsigned errors (MUEs) of 1.00 and 0.73 kcal mol –1 for the DBH76 and HTBH38 data sets involving hydrogen-transfer barrier heights, respectively .…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
“…In addition, for reactions at atmospheric temperatures, it is normally found that accounting for all conformers explicitly by summing their individual contributions, even in a simple RR-HO approximation, recovers most of the nonharmonicity introduced by the internal rotation, since the molecules will reside mostly in the thermally weighted lower-energy harmonic wells . Moreover, variational and recrossing effects may also have an important contribution, as they are known to decrease the rate contants sometimes significantly . In contrast, the simple and inexpensive one-dimensional Eckart tunneling correction is frequently able to reproduce expensive and robust multidimensional transmission coefficients, such as the small curvature tunneling (SCT) correction, at a very low computational cost.…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Including these effects in ME calculations requires considerable extra effort . Multidimensional tunneling methods can be crucial to accurately describe certain chemical reactions even at relatively high temperatures (∼700 K), , and multistructural anharmonicity can be pronounced in reactions involving complex molecules in the high-temperature regime; , these effects can be efficiently incorporated in low-pressure rate constant calculations by the SS-QRRK theory, , justifying the need for further improvements of this methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Although direct kinetic measurements are difficult under the elevated T – P conditions, the theoretical calculation has proven to be an alternative approach to predict the combustion kinetics in a wide range of temperatures and pressures. A few theoretical studies on the MBO232 + OH reaction have been carried out. Baasandorj and Stevens investigated the stability of the two initial adducts of the MBO232 + OH reaction at the B3LYP/6-31G­(d,p) and B3LYP/6-311+G­(d) levels.…”
Section: Introductionmentioning
confidence: 99%